European human rights and family law - Choudhry, Shazia; Herring, Jonathan (Oxford ; Portland, Or. : Hart, 2010)
'European Human Rights and Family Law' assesses the impact of the Human Rights Act on family law and explores changes Article 8 (the right to respect for family life) will make to related areas of law.
The European Convention on Human Rights and family law -- The Human Rights Act : scheme, principles and implementation -- Human rights in family law -- Marriage -- Parenthood and parental rights : intention, family life and the parent -- Children's rights -- Private law children cases : a rights perspective -- Human rights and child protection -- Domestic violence : the extent of the problem and the recognition and use of a human rights discourse -- Financial disputes and human rights -- Concluding thoughts.
Includes bibliographical references and index.
Keywords: Domestic relations -- Great Britain; Domestic relations -- Europe; Civil rights -- Great Britain; Human rights -- Europe; Civil rights; Domestic relations; Human rights; Europe; Great Britain